Adenocalymma ubatubensis Assis and Semir, a new species of Bignoniaceae from Ubatuba, Sao Paulo State, Brazil - Assis, Marco Antonio [UNESP]; Semir, João (My University, 1999)
Adenocalymma ubatubensis, a new species from southeastern coastal Brazil, is described and illustrated. The species is distinguished by its large pseudostipules and calyx without nectaries.
Keywords: Adenocalymma ubatubensis